PEMBELAJARAN SENI TARI DALAM MEWUJUDKAN ASPEK PERKEMBANGAN ANAK DI TAMAN KANAK-KANAK PETERI BENSU TAKENGON - Eliyyil Akbar; Jainal Abidin (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2018)
Discussions about children can never stop because of their unique nature. The uniqueness of children can not be responded by adults so that the pattern of education is more restraining and requires following the will of the adult mind so that it makes it difficult for children to accept and have an impact on the aspects of child development. The problem solving task is at a children's education institution by providing dance learning as a fun learning experience for children so that aspects of child development can be realized. This method uses field research with sampling or data source determination using purposive sampling. Data collection uses observation, interviews and documentation and is analyzed by means of data reduction, data display, and conclusion drawing / verification. This paper aims to review how the development of religion and morals, motor development, cognitive development, language development, social emotional development of children can be realized through dance art education. The results of this study are (1) Aspects of religious and moral development that are realized through dance can be done with movements that have behavioral indicators as applicable. If it is associated with a movement that is processed with the existence of certain objectives, it can be done by doing a movement that matches the value of goodness. (2) Aspects of motor development through dance or the beauty of a movement are seen in two parts, namely fine motor and gross motor. Fine motorization focuses the coordinate point of the hand movement by using a property in the dance while the gross motor is based on movements involving the whole body. (3) Cognitive development through dance art is seen in the aspect of children's thinking where every movement that arises in motor pressure is influenced by the results of thinking that explores the part of the brain. (4) The development of language through dance is seen in children's activities which are internalized in a word from the response of a rhythmic beauty and then responded by the whole body so that the spoken song is accompanied by a movement. (5) Child's social and emotional development can develop through dance education through a feeling produced. The ability of the child in motion is a response to the feeling in the child. This can be seen in the actualization of movements that appear with explicit themes, themes that tell about sadness or happiness make a diverse feeling. Social development cannot be separated from the interaction between dancers and viewers and between the dancers.